Efeito da temperatura e do fotoperíodo sobre o crescimento e desenvolvimento de caju - Matos, Victor Arlindo Taveira de (2013)
The purpose of this study was to identify the base temperatures to complete the maturation process of three clones of dwarf cashew trees: FAGA 1, FAGA 10 and FAGA 11. Daily data on air temperature were used, provided by Padre Ricardo Remetter Meteorological Station, situated at the UFMT’s Experimental Farm, which is located in Santo Antonio do Leverger, MT (15.8 ° S and 56.1 ° W, 140 m), where this work was conducted. Were employed the thermal sum method (TS), Wang & Engel nonlinear model (WE) and the photo thermal units (UF). The approximations using TS method (for the three clones) and the WE model (for the FAGA 1 and for the FAGA 10) were most useful than the count of chronological time in predicting the physiological time necessary to complete the process of fruit ripening. It was also found that the studied clones presented, under the cerrado conditions in the Baixada Cuiabana, length and diameter of pseudo fruit and fruit (cashew nut), within market standards and, in the pseudo fruits, superior levels of total soluble solids. The model of photo thermal units was not adequated to studies conditions.